Nano/Micro Science and Technology in Biorheology: Principles, Methods, and Applications - Kita, Rio (Springer, 2016)
Integrating basic to applied science and technology in medicine, pharmaceutics, molecular biology, biomedical engineering, biophysics and irreversible thermodynamics, this book covers cutting-edge research of the structure and function of biomaterials at a molecular level. In addition, it examines for the first time studies performed at the nano- and micro scale. With innovative technologies and methodologies aiming to clarify the molecular mechanism and macroscopic relationship, Nano/Micro Science and Technology in Biorheology thoroughly covers the basic principles of these studies, with helpful step-by-step explanations of methodologies and insight into medical applications. Written by pioneering researchers, the book is a valuable resource for academics and industry scientists, as well as graduate students, working or studying in bio-related fields.